Juridical Study Dispute Settlement Process Cancellation of Sale and Purchase of Land Rights and Joint Assets - Inaya Putri, Nazira; Octarina, Nynda Fatmawati (Al-Risalah Jurnal Ilmu Syariah dan Hukum, 2022)
The research was conducted aiming to find out how the process of settlement of land sale and purchase disputes was carried out. The research was conducted with reference to the applicable laws and regulations. Data analysis using data equations that have been obtained at the time of the study finally obtained the following research results: (1) Based on the decision of the case Number: 62/Pdt.G/2013/PN. Tk is a problem in the implementation of the sale and purchase of joint assets carried out without the consent of one of the parties. The decision of the panel of judges in Decision Number : 62/Pdt.G/2013/PN.Tk which rejected the plaintiff’s claim was correct. This is because the disputed land is not a joint property (gono gini) of the Plaintiff and Defendant II. Defendant II did not act for himself but only served as a "proxy". The position of Defendant II who only acts as the "power" to sell the disputed land is reasonable because as has been considered above.